2014
DOI: 10.4028/www.scientific.net/amm.592-594.705
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Mechanical Characterization of Stir Cast Hybrid Al7075-Al<sub>2</sub>O<sub>3 </sub>-B<sub>4</sub>C Metal Matrix Composites

Abstract: A hybrid Al7075 metal matrix composites have been fabricated through liquid metallurgy route (Stir Casting method) using Al2O3 and B4C as reinforcement materials. The effect of weight percentage of reinforcement materials on mechanical properties of the composites have been studied by varying the weight percentage of Al2O3 as 3, 6, 9, 12 and 15% while keeping constant weight percentage of B4C (3%). The as-cast microstructure, tensile strength, micro and macro hardness of the fabricated hybrid composites have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Generally, the hard ceramic particles avoid the motion of dislocations which leads to improvement in the results of hardness [30]. As the hard ceramic reinforcements are added, the hardness is increased, which exhibits more resistance to plastic deformation with in the composite rendering increase in hardness of the composites [31]. Similar outcomes were observed by Rajesh Kumar Bhushan [10] the results conclude that the silicon carbide particles form barricades which hinder the dislocation motion.…”
Section: Hardnesssupporting
confidence: 59%
“…Generally, the hard ceramic particles avoid the motion of dislocations which leads to improvement in the results of hardness [30]. As the hard ceramic reinforcements are added, the hardness is increased, which exhibits more resistance to plastic deformation with in the composite rendering increase in hardness of the composites [31]. Similar outcomes were observed by Rajesh Kumar Bhushan [10] the results conclude that the silicon carbide particles form barricades which hinder the dislocation motion.…”
Section: Hardnesssupporting
confidence: 59%
“…This is owing to the reinforcement particles serving as tensile stress resistance, as well as the strengthening mechanism via reinforcement load factor in the produced sample. B 4 C and Al 2 O 3 -reinforced Al7075 matrix composites were prepared by Dhanalakshmi et al [92] through stir casting method, and they observed increase in hardness and tensile strength of the composites with increase in the weight percentage of B 4 C particulates in the aluminum matrix. This is consistent with the findings of Selvam et al [93], who used SiC and fly ash as reinforcing materials and obtained similar results.…”
Section: Nomentioning
confidence: 99%
“…Dhanalakshmi et al [92] investigated the influence of Al2O3/B4C particles on structure and mechanical properties of AA7075/Al2O3/B4C AMC which were fab through the liquid metallurgy route (stir casting method). In the mechanical char tics of the composites, the influence of the mass percentage of reinforcing elements weight of Al2O3 varied by 3, 6, 9, 12, and 15 wt.%, while the B4C weight percenta constantly maintained (3%).…”
Section: Hardness Of Hamcmentioning
confidence: 99%
“…Many endeavors have been made to additionally work on the mechanical properties of the 7075 aluminum chemical. Improvement in the exhibition of most aluminum combinations can be credited to adjustments to chemical synthesis and additionally utilizing new fabrication strategies [18]. Al7075 are significant chemicals among 7xxx series aluminum combination assignments and are generally utilized in safeguard areas because of intrinsic properties like light weight and high strength materials when contrasted with solid materials [19].…”
Section: Introductionmentioning
confidence: 99%